Making precision medicine personal for cystic fibrosis - Manfredi, Candela; Tindall, Janice M.; Hong, Jeong S.; Sorscher, Eric J. (Science (American Association for the Advancement of Science), 2019)
Molecular defects in the cystic fibrosis gene prompt creative approaches to treatment Cystic fibrosis (CF) is an inherited, life-threatening disease that primarily involves exocrine tissues (such as lungs, pancreas, and liver) for which highly active pharmacotherapies have recently emerged. More than 1700 disease-associated variants are described in the CF transmembrane conductance regulator ( CFTR ) gene, which encodes an epithelial cell ion channel that is defective in patients with CF. On the basis of classifying CFTR mutant proteins according to pathogenic mechanisms, the disease has been viewed as a model for personalized therapeutics. However, CFTR variants may have pleiotropic effects, which complicates assignment of specifically tailored drugs to discrete mechanistic subcategories. In addition, the cost of new CFTR modulators constrains third-party reimbursement and has delayed drug availability for certain patient groups, including individuals with ultrarare CFTR variants for which the treatments are not formally approved but may still be effective. Issues such as these are being addressed by innovative and powerful approaches to promote CF precision medicine.